Implementasi Dan Analisis Server Bigbluebutton Dalam Pemanfaatan Meeting Online Pada Masa Pandemic - Kusuma, Alan Budi; Yusuf, Amir; Hidayat, Alfian (Walisongo Journal of Information Technology, 2020)
The need for videoÂ converence is something that cannot be ignored. Amid the Covid-19 pandemic outbreak all sectors must utilize this technology. Such is the case with Semarang Islamic State University Walisongo. Where UIN Walisongo requires all students, lecturers and education personnel to remain at home in an effort to comply with government regulations as an effort to prevent this outbreak. Therefore, to find a solution for communication to stay connected, a system for online meetings was built that could be used by students and lecturers as a medium of online learning, and the education staff and leaders to be able to always be connected in the midst of the covid outbreak.